Analysis of the Modification and Backlash of High Precision Cycloid Drive - Hou Nai; Wang Changlu; Zhang Liyong; Huang Shoufeng; Zhou Hongkai; Li Yakang (Jixie chuandong)
The backlash is an important indicator of cycloid drive,and the modification is a major factor.Comprehensively considering the bearing capacity and backlash of the whole machine,the modification optimization of the cycloid gear is carried out by using the Matlab optimization tools,and a conclusion that high precision cycloid drive adopting " negative equidistance + negative shift" composite modification will get ideal cycloid gear profile is obtained.